Design and implementation of a real-time data acquisition system for the identification of dynamic temperature models in a hydroponic greenhouse - Ferreira, P. M. (2013)
This text describes a real data acquisition and identification system implemented in a soilless greenhouse located at the University of Algarve (south of Portugal). Using the Real Time Workshop, Simulink, Matlab and the C programming language a system was developed to perform real-time data acquisition from a set of sensors.